Microstructure and Electrochemical Properties of Pure and Vanadium-Doped Li4Ti5O12 Nanoflakes for High Performance Supercapacitors - Mudda Deepak; Obili M. Hussain; Christian M. Julien (Inorganics)
Nanostructured binary metal oxides have demonstrated the potential for increased electrochemical performance due to their structural stability, electronic conductivity, and various oxidation states. The Li4Ti5O12 was successfully synthesized via a hydrothermal procedure at different reaction periods (12, 18, and 24 h), and its microstructural and supercapacitive characteristics were studied. The XRD and XPS studies confirm the formation of Li4Ti5O12 in pure phase when synthesized at 24 h (LTO@24) of reaction time. FESEM and HRTEM images reveal nanoflake surface morphology. Both LTO@24 and V-LTO@24 nanoflakes exhibited impressive electrochemical performance, with specific capacitance values of 357 and 442 F g−1, respectively, at 1 A g−1. The V-LTO@24 showed remarkable supercapacitor properties, demonstrating excellent rate capability and cycleability that surpass those of pure LTO@24.